Audit of minimally-invasive surgery for submandibular sialolithiasis. Issue 6 (July 2019) - Holden, A.M.; Man, C.-B.; Samani, M.; Hills, A.J.; McGurk, M.
Abstract: Sialolithiasis is one of most common diseases to affect major salivary glands, with a symptomatic incidence of 27 cases per million per annum. The majority form within the submandibular gland where minimally-invasive treatments have all but eliminated adenectomy. All records of patients presenting with submandibular stones between 1997 and 2015 were reviewed. Stones <5 mm were retrieved through endoscopic or radiographic techniques, 5-7 mm stones were initially considered for extra-corporeal shock wave lithotripsy, but after poor results were treated through intraoral surgical removal with those >7 mm. Follow up was performed at 1 week and 3 months with current status performed with postal and telephone questionnaires. 378 patients had 424 stones removed, successful retrieval in 94% (n = 356), with 50 having had previous failures. Median number of stones per patient was 1 (range 1-4), with a mean size of 8.6 mm (SD 4.5 mm) mainly located at the hilum (50.5%), anterior duct (30%) and Genu (17%). 256 patients (65%) treated through intraoral surgical extraction, 92 (24%) endoscopic alone. Inpatient stay was 1.4 days in first third and 0.5 days in final third. Adenectomy occurred in 14 patients, due to failure to retrieve the sialolith or unresolved symptoms. Complications involved 11 patients with permanent paraesthesia, 7 ranulas and 14 strictures. Patients with preoperative strictures were more likely to develop complications (p = 0.002) with paraesthesia being most common. Intraoral minimally-invasive surgery is aesthetic, curative and spares the risk to marginal mandibular nerve and submandibular gland. Length of inpatient stay improved and ranula risk reduced throughout the study.